2015
DOI: 10.1017/s1743921315008558
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the stellar halos of six massive disk galaxies beyond the Local Group

Abstract: Models of galaxy formation in a hierarchical universe predict substantial scatter in the halo-to-halo stellar properties, owing to stochasticity in galaxies' merger histories. Currently, only few detailed observations of stellar halos are available, mainly for the Milky Way and M31. We present the stellar halo color/metallicity and density profiles of red giant branch stars out to ~60 kpc along the minor axis of six massive nearby Milky Way-like galaxies beyond the Local Group from the Galaxy Halos, Outer disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…We measure an RMS scatter of 1.01 +0.09 −0.26 dex, and a peak-to-peak span of a factor of > 100. This level of stochasticity is high and certainly exceeds the expectations (Amorisco et al 2015;Cooper et al 2010Cooper et al , 2013 from numerical simulations (the grey regions shown in the Figure ), though they may be qualitatively consistent with variations in the structure and stellar populations of nearby stellar haloes observed in both integrated light and star counts studies (e.g., Mouhcine et al 2007;Barker et al 2012;Monachesi et al 2015). The former may be contaminated by scattered light, and the latter (based on pencil beams) may not be fairly sampling the haloes, so the Dragonfly observations provide a robust baseline for future characterization of the stellar halo mass fraction in luminous nearby spirals.…”
Section: Galactic Outskirtssupporting
confidence: 74%
“…We measure an RMS scatter of 1.01 +0.09 −0.26 dex, and a peak-to-peak span of a factor of > 100. This level of stochasticity is high and certainly exceeds the expectations (Amorisco et al 2015;Cooper et al 2010Cooper et al , 2013 from numerical simulations (the grey regions shown in the Figure ), though they may be qualitatively consistent with variations in the structure and stellar populations of nearby stellar haloes observed in both integrated light and star counts studies (e.g., Mouhcine et al 2007;Barker et al 2012;Monachesi et al 2015). The former may be contaminated by scattered light, and the latter (based on pencil beams) may not be fairly sampling the haloes, so the Dragonfly observations provide a robust baseline for future characterization of the stellar halo mass fraction in luminous nearby spirals.…”
Section: Galactic Outskirtssupporting
confidence: 74%